2019
DOI: 10.1073/pnas.1817972116
|View full text |Cite
|
Sign up to set email alerts
|

Dated language phylogenies shed light on the ancestry of Sino-Tibetan

Abstract: The Sino-Tibetan language family is one of the world’s largest and most prominent families, spoken by nearly 1.4 billion people. Despite the importance of the Sino-Tibetan languages, their prehistory remains controversial, with ongoing debate about when and where they originated. To shed light on this debate we develop a database of comparative linguistic data, and apply the linguistic comparative method to identify sound correspondences and establish cognates. We then use phylogenetic methods to infer the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
141
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 53 publications
12
141
1
1
Order By: Relevance
“…It has therefore been proposed that Neolithic people living at least 6 kya (Yang et al, 2012) or before 9 kya (van Driem, 2005) in northwestern China were probably the ancestors of modern ST populations. It has also been suggested that Sino-Tibetan languages originated among millet farmers, located in North China, around 7.2 kya (Sagart et al, 2019) or 5.9 kya (Zhang et al, 2019). Linguistic evidence then suggests differentiation between Sinitic and Tibeto- Burman languages, and also between Tibetan and Lolo-Burmese languages, and southward and westward expansions of ST groups (Sagart et al, 2019; Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has therefore been proposed that Neolithic people living at least 6 kya (Yang et al, 2012) or before 9 kya (van Driem, 2005) in northwestern China were probably the ancestors of modern ST populations. It has also been suggested that Sino-Tibetan languages originated among millet farmers, located in North China, around 7.2 kya (Sagart et al, 2019) or 5.9 kya (Zhang et al, 2019). Linguistic evidence then suggests differentiation between Sinitic and Tibeto- Burman languages, and also between Tibetan and Lolo-Burmese languages, and southward and westward expansions of ST groups (Sagart et al, 2019; Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The ST family originated in northern China ~7 kya (Sagart, et al 2019;) and 29 then started to move southward into MSEA ~3 kya (Bellwood 2015). Compared to HM and TK 30 groups, the ST groups form a relatively independent and isolated cluster (figs.…”
Section: Sino-tibetan 28mentioning
confidence: 99%
“…The Chinese language has more than three thousand years of history (see, for example, [4,5,[11][12][13]). It is one of two branches of the Sino-Tibetan (ST) language family of languages.…”
Section: Introductionmentioning
confidence: 99%
“…ST language family is one of the world's largest and most prominent families, spoken by nearly 1.4 billion people [13]. As it is noted in [13], despite the importance of the ST languages, their prehistory remains controversial, with ongoing debate about when and where they originated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation